2018
DOI: 10.2298/abs171004047v
|View full text |Cite
|
Sign up to set email alerts
|

Post-metamorphic ontogenetic changes in head size and shape of the pool frog (Pelophylax lessonae, Ranidae)

Abstract: How to cite this article: Vukov TD, Kuručki M, Anđelković M, Tomašević Kolarov N. Post-metamorphic ontogenetic changes in head size and shape of the pool frog (Pelophylax lessonae, Ranidae).Abstract: Post-metamorphic ontogenetic variations of head size and shape were investigated in the pool frog (Pelophylax lessonae, Ranidae). We showed that allometry is an important aspect of the post-metamorphic ontogeny of the pool frog as most of the differences between the head shape of subadults and adults were size-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Concerning relative body size (expressed as snoutvent length in herpetology), most of P. pueyoi are around 9 cm (with the largest ones reaching around 10.5 cm; McNamara et al, 2009). Such a body size is well beyond the maximum observed in the extant P. lessonae (reaching 4-7 cm in adults; i.e., Vukov et al, 2018) and P. quellembergi (reaching 7.5 cm), but inside the maximum body size observed for most of extant European Pelophylax, as Pelophylax perezi and P. ridibundus (around 8 cm for adults, but reaching up to 11 cm for females; i.e., Egea-Serrano, 2014). In herpetology, approximation to head width is given by the relation between head width and snout-vent length (HW/SVL).…”
Section: Discussion and Diagnosismentioning
confidence: 93%
See 1 more Smart Citation
“…Concerning relative body size (expressed as snoutvent length in herpetology), most of P. pueyoi are around 9 cm (with the largest ones reaching around 10.5 cm; McNamara et al, 2009). Such a body size is well beyond the maximum observed in the extant P. lessonae (reaching 4-7 cm in adults; i.e., Vukov et al, 2018) and P. quellembergi (reaching 7.5 cm), but inside the maximum body size observed for most of extant European Pelophylax, as Pelophylax perezi and P. ridibundus (around 8 cm for adults, but reaching up to 11 cm for females; i.e., Egea-Serrano, 2014). In herpetology, approximation to head width is given by the relation between head width and snout-vent length (HW/SVL).…”
Section: Discussion and Diagnosismentioning
confidence: 93%
“…In herpetology, approximation to head width is given by the relation between head width and snout-vent length (HW/SVL). This ratio is 0.341 ± 0.012 (n: 13; min/max: 0.322/0.359; Crochet et al, 1995) for P. perezi , 0.376 ± 0.015 (n: 5; min/max: 0.353/0.393; Crochet et al, 1995) for P. ridibundus , and 0.341 (n: 36; Vukov et al, 2018) for P. lessonae . The same ratio for MPZ 2022/579 can be estimated around 0.384, thus entering inside the modern upper range of P. ridibundus and the lower range of P. pueyoi (0.399 ± 0.039; n = 20; min/max = 0.348/0.493), but well beyond the ranges of P. quellembergi (0.330 ± 0.030, n = 3; min/max: 0.300/0.357), P. perezi , and P. lessonae .…”
Section: Discussion and Diagnosismentioning
confidence: 96%
“…The vertebrate head size correlates with some important biological functions, such as predation, mate acquisition and locomotion (Vukov et al, 2018). The sexual dimorphism in head size may be correlated with allometry (Dursun et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The wider heads in males may indicate their proportionally higher consumption rate of bulky prey (Mebert, 2011), which allows them to obtain broad food resources and meet the high energy consumption during reproduction (Yao et al, 2020). Also, the wider head could accommodate larger jaw muscles and increase the bite force (Vukov et al, 2018), which are advantageous in male–male combat and greater access to females (Lappin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers found that subtle structural differences in the proportion of hindlimbs would facilitate functional diversity, allowing for wide-ranging exploitation of environments (Duellman & Trueb, 1994;Emerson, 1978;Emerson, 1979;Emerson, 1983;Emerson, 1985;Emerson & De Jongh, 1980;Nauwelaerts, Ramsay & Aerts, 2007). Ontogenetic processes have been considered responsible of the morphological variability among species and could have a profound impact on the shape of morphological structures (Thompson, 1942;Gould, 1977;Alberch, Gould & Wake, 1979;Calder III, 1984;Schmidt-Nielsen, 1984;Emerson & Bramble, 1993;Reilly, Wiley & Meinhardt, 1997;Vukov et al, 2018). However, few studies have investigated the ontogenetic variation of the musculotendinous system, which could be responsible for generating and transmitting force to produce and control body movements.…”
Section: Introductionmentioning
confidence: 99%